SUSTAINABLE FISH RESOURCES POTENTIAL IN MANGROVE FOREST AREAS AFFECTED BY TIN MINING IN THE BANGKA BELITUNG ISLANDS PROVINCE - endang bidayani (Politeknik Kelautan dan Perikanan Karawang, BRSDM KP., 2026)
Several areas on Bangka and Belitung Islands are located in tin mining conflict zones. Therefore, it is feared that this will threaten the existence of fish resources in mangrove forest areas. The objectives of this study are: 1) To analyze the perceptions of local communities for mangrove resources on Bangka and Belitung Islands, and 2) To assess the sustainable potential of fish resources in mangrove forest areas on Bangka and Belitung Islands. This research method is a survey method. The determination of the research location was purposive, namely six coastal villages that have mangrove forests and are tin mining conflict areas, namely three villages on Bangka Island, including Kota Waringin Village, Kota Kapur Village and Sungaiselan Village, and three villages on Belitung Island, including Gantung Village, Lassar Village and Buding Village. The population in this study were traditional fishermen, community leaders, and village government as informants totaling 60 people. Data collection methods in this study include primary data and secondary data. Primary data collection used questionnaires, in-depth interviews, observation and documentation. Secondary data collection through literature studies. The data analysis method used is exploratory descriptive method. The results of the study, the perception of traditional fishermen towards fish resources in the mangrove forest area on Bangka and Belitung Islands in the Good category, and 2) The sustainable potential of fish resources in the mangrove forest area on Bangka and Belitung Islands using the Schafer model with the CYP technique (Clarck, Yoshimoto, Pooley) shows that the optimal catch results based on Maximum Sustainable Yield (MSY) of 271,95 tons.